“New Minorities” in the States Parties to the Framework Convention: The Importance of Self-Identification and Recognition - Dragan, Andrei (Pécs journal of international and European law, 2018)
This paper aims to present some of the issues faced by minorities, especially “new minorities”, namely lack of recognition as such and societal acceptance, mainly in the countries part to the Framework Convention for the Protection of National Minorities, as well as the exclusion from citizenship status and, in general, from how the majority society (or even other, “established” minorities) define their nation. I contend that this exclusion stems from a state of denial that most European societies are in, which determines a lack of recognition of factual diversity. And although some improvements can be applauded, especially in the case of easing the criteria for citizenship, the general societal, legal and political situation in Europe points to a less than satisfying image. As such, another aim of this paper is to reveal the importance of individual self-identification of persons belonging to minorities and of recognition of the identities that result from this (mostly) internal process by their peers and by their “host” states.